The Effect of Cultural Differences on Behavioral Responses to Low Job Satisfaction - Thomas, David C.; Au, Kevin (Journal of International Business Studies, 2002)
This article reports the results of a field study that evaluated behavioral responses to low job satisfaction of participants in Hong Kong and New Zealand. Culture, measured by vertical and horizontal individualism and collectivism, had both main and moderating effects on responses. First, cultural groups responded differently to low job satisfaction with exit, voice, loyalty, or neglect. Second, culture moderated the effect of quality of job alternatives and job satisfaction on exit and loyalty, and moderated the effect of quality of job alternatives on voice.